Bim establishes the B-cell repertoire from early to late in the immune response - Sugimoto-Ishige, Akiko; Harada, Michishige; Tanaka, Miho; Terooatea, Tommy; Adachi, Yu; Takahashi, Yoshimasa; Tanaka, Takashi; Burrows, Peter D; Hikida, Masaki; Takemori, Toshitada (International immunology, 2021)
Abstract In T cell-dependent antibody responses, some of the activated B cells differentiate along extrafollicular pathways into low-affinity memory and plasma cells, whereas others are involved in subsequent germinal center (GC) formation in follicular pathways, in which somatic hypermutation and affinity maturation occur. The present study demonstrated that Bim, a proapoptotic BH3-only member of the Bcl-2 family, contributes to the establishment of the B-cell repertoire from early to late stages of immune responses to T cell-dependent antigens. Extrafollicular plasma cells grew in the spleen during the early immune response, but their numbers rapidly declined with the appearance of GC-derived progeny in wild-type mice. By contrast, conditional Bim deficiency in B cells resulted in expansion of extrafollicular IgG1+ antibody-forming cells (AFCs) and this expansion was sustained during the late response, which hampered the formation of GC-derived high-affinity plasma cells in the spleen. Approximately 10% of AFCs in mutant mice contained mutated VH genes; thus, Bim deficiency appears not to impede the selection of high-affinity AFC precursor cells. These results suggest that Bim contributes to the replacement of low-affinity antibody by high-affinity antibody as the immune response progresses. Bim regulates B-cell dynamics as immune responses mature